Rynek długoterminowych kapitałów pieniężnych w strukturze rynku kapitałów pieniężnych - Gruszczyńska-Brożbar, Elżbieta (Wydział Prawa i Administracji UAM, 1999)
The systematic of financial capital markets is not homogeneous. Contemporarily used in Polish literature criteria of disaggregation of financial market into-money market and capital market seem to be too enigmatic. Classic literature of the subject, as well Polish as world-wide, strays from such a canon division. Some of classifications presented in the article are rather artificial, however a majority of them is based on monitoring changes that do constitute circulation money and economic development. The article is presenting criteria of division of financial capital markets with particular reference to objects structure of the market of long-term financial capitals. Main lines of division of this market - as applied in English and German literature - are indicated. They are compared, too, with those applied once in classical positions of Polish scientific output as well as with other national papers which occurred to be questioned by some of the experts. Final part of the article is devoted to the Authors’ attempt of an own interpretation (if not: new further segmentation) of the market of long-term financial capitals within the structure of financial capital - with having recourse to sharper criteria of this proposed division.
A market of long-term financial capitals within the structure of financial capitals market